Field-Effect Device Using Quasi-Two-Dimensional Electron Gas in Mass-Producible Atomic-Layer-Deposited Al2O3/TiO2 Ultrathin (<10 nm) Film Heterostructures - Seok, Tae Jun; Liu, Yuhang; Jung, Hae Jun; Kim, Soo Bin; Kim, Dae Hyun; Kim, Sung Min; Jang, Jae Hyuck; Cho, Deok Yong; Lee, Sang Woon; Park, Tae Joo (ACS Nano, 2018)
We report the field-effect transistors using quasi-two-dimensional electron gas generated at an ultrathin (∼10 nm) Al2O3/TiO2 heterostructure interface grown via atomic layer deposition (ALD) on a SiO2/Si substrate without using a single crystal substrate. The 2DEG at the Al2O3/TiO2 interface originates from oxygen vacancies generated at the surface of the TiO2 bottom layer during ALD of the Al2O3 overlayer. High-density electrons (∼1014 cm-2) are confined within a ∼2.2 nm distance from the Al2O3/TiO2 interface, resulting in a high on-current of ∼12 μA/μm. The ultrathin TiO2 bottom layer is easy to fully deplete, allowing an extremely low off-current, a high on/off current ratio over 108, and a low subthreshold swing of ∼100 mV/decade. Via the implementation of ALD, a mature thin-film process can facilitate mass production as well as three-dimensional integration of the devices.
Keywords: Atomic layer deposited; Field-effect devices; Heterostructure interfaces; ON/OFF current ratio; Quasi-two-dimensional electron gas; Single crystal substrates; Subthreshold swing; Three dimensional integration; aluminum oxide; atomic layer deposition; field-effect transistor; titanium oxide; two-dimensional electron gas